New insights into the mechanisms of electroconvulsive therapy in treatment-resistant depression - Ruiz, Ana C.; Haseeb, Abdul; Baumgartner, William; Leung, Edison; Scaini, Giselli; Quevedo, Joao (Frontiers in Psychiatry, 2025)
Electroconvulsive therapy (ECT) remains one of the most effective interventions for treatment-resistant depression (TRD), particularly in cases involving severe symptomatology, suicidality, or psychotic features. Despite advancements aimed at enhancing the safety and cognitive tolerability of ECT, concerns about cognitive side effects continue to limit its broader acceptance. A deeper understanding of the mechanisms underlying ECT is therefore critical for refining its use and maximizing clinical outcomes. Through a narrative review of recent literature, this paper synthesizes current evidence comparing the efficacy of ECT, ketamine, and repetitive transcranial magnetic stimulation (rTMS) in the treatment of TRD. Then, the review delves into the neurobiological mechanisms through which ECT exerts its therapeutic effects, including modulation of neurotransmitter systems, enhancement of neurogenesis, changes in brain network connectivity, immune response regulation, neurotrophic signaling, and epigenetic alterations. These mechanistic insights may inform the identification of biomarkers predictive of treatment response. Moving forward, future research guided by interaction mechanisms hypotheses could provide more insights into alternative neuromodulation techniques, optimize ECT procedures, and improve patient-specific treatment approaches to enhance therapeutic benefits while minimizing adverse effects.